Regulations for Use of Geosynthetics for Road Embankments and Subgrades - Audrius Vaitkus; Aurimas Šiukščius; Vaidas Ramūnas (The Baltic Journal of Road and Bridge Engineering)
The increased use of geosynthetics in road constructions has resulted in a need to better understanding of geosynthetics properties for the use in design and quality control. For this purpose, the regulations for use of geosynthetics for road embankments and subgrades were created in Lithuania. It was found that other European countries such as Germany and United Kingdom use not only harmonised European standards, but also has their own regulations for geosynthetics. This study indicates the relationship between regulations in Lithuania and other countries. Calculation conception and regulations for controlling characteristics were introduced first time in Lithuanian road construction market. The use of those regulations will increase the quality of construction and life time of road pavement structures.